P835 Correlation between microbial markers and faecal calprotectin in IBD patients. (15th January 2020) - Amoedo Cibeira, J; Ramió-Pujol, S; Serra-Pagès, M; Bahí, A; Puig-Amiel, C; Oliver, L; Gilabert, P; Clos, A; Mañosa, M; Cañete, F; Miquel-Cusachs, J O; Torrealba, L; et al.
Abstract: Background: Crohn disease (CD) and Ulcerative colitis (UC) are characterised by episodes of exacerbations and remissions. Monitoring disease activity based on intestinal lesion is mandatory prior to any change in the therapeutic strategy. Colonoscopy is the gold standard technique to monitor the disease activity in IBD patients, but it is usually discarded because of costs and risk issues. The concentration of Faecal Calprotectin (FC) is widely used as a non-invasive marker of inflammation of the intestinal mucosa, allowing the assessment of the disease activity. Recently, different studies have demonstrated that certain microbial species, part of intestinal microbiota which can be detected in stool samples, are capable of correlating with disease activity in CD and UC patients. The purpose of this study was to analyse the correlation between these microbial indicators and the FC to monitor the disease activity in CD and UC patients. Methods: FC levels were used to define inflammatory disease activity, the predetermined cut-off of 250 μg/g of faeces was used, higher values indicated an active inflammation and lower values indicated disease in remission. Two cohorts consisting of 61 patients of CD (25 with active inflammation and 36 with remission) and 90 of UC (42 with active inflammation and 48 with remission) were recruited by the Gastroenterology department of 4 Catalan hospitals. A sample of faeces was collected from each patient. FC and the following markers were quantified by qPCR: Faecalibacterium prausnitzii (Fpra), Escherichia coli (Eco), Akkermansia muciniphila (Akk), Ruminococcus sp. (Rum), Bacteroidetes (Bac) and Methanobrevibacter smithii (Msm) for each sample. Results: The bacterial markers presented different behaviour depending on the disease analysed. The abundances of Eco and Bac were higher in CD with active inflammation compared with CD with remission. In contrast, no significant differences were found for Fpra, Akk, Rum, and Msm. Besides, a significant positive correlation between Eco abundance and FC levels (0.280, p = 0.029) and a significant negative correlation between Msm and FC levels (−0.299, p = 0.021) were observed. According UC patients, while the abundance of Eco was higher in patients with active inflammation, the abundance of Rum was significantly less abundant. No significant differences were found for Fpra, Akk, Bac, and Msm. Moreover, we also observed a significant negative correlation between Rum and FC levels (−0.308, p = 0.003, respectively). Conclusion: The abundance of Eco and Msm in CD patients and the abundance of Rum in UC patients correlate to FC in order to determine inflammatory disease activity. So, these markers can also be an accurate discriminator of active disease in CD and UC patients.